Hydrogen storage in ion-exchanged zeolites - Langmi, H; Book, D; Walton, A; Johnson, SR; Al-Mamouri, M; Speight, J; Edwards, P; Harris, I; Anderson, P (2005)
The hydrogen storage properties of zeolites X, Y, A and Rho containing various exchangeable cations have been investigated. All hydrogen storage capacities were measured at a temperature of -196° C and a pressure range of 0-15 bar, using a constant pressure thermogravimetric analyser. The results show that, zeolites exhibit diverse behaviour with respect to hydrogen uptake, dependent on both the framework structure and the nature of the cations present. A major factor influencing uptake is the available void space: in zeolites A and Rho pore blocking by large extraframework cations is a major factor restricting hydrogen uptake, but in zeolites X and Y, blocking does not occur. This study also suggests that cations may act as binding sites for hydrogen molecules. For zeolites X and Y, hydrogen uptake relates closely to the measured BET surface area. The highest gravimetric storage capacity of 2.19 wt.% was obtained for CaX. Volumetric storage densities of up to 31.0 kg H 2/m3 (143 H2 molecules/unit cell) and 30.2 kg H2/m3 (144 H2 molecules/unit cell) were achieved for CaX and KX, respectively. © 2005 Elsevier B.V. All rights reserved.